Epigenetics and cancer metabolism. Issue 2 (28th January 2015) - Johnson, Christelle; Warmoes, Marc O.; Shen, Xiling; Locasale, Jason W.
Highlights: Epigenetic modifications regulate cellular functions in health and disease, notably tumorigenesis. Cancer cells are characterized by metabolic alterations that support their growth and survival. Metabolic and epigenetic enzymes are often components of the same framework that sustains cancer development and progression. Novel anti-cancer therapy focuses on intercepting metabolic networks and epigenetic reactions that promote tumorigenesis. Abstract: Cancer cells adapt their metabolism to support proliferation and survival. A hallmark of cancer, this alteration is characterized by dysfunctional metabolic enzymes, changes in nutrient availability, tumor microenvironment and oncogenic mutations. Metabolic rewiring in cancer is tightly connected to changes at the epigenetic level. Enzymes that mediate epigenetic status of cells catalyze posttranslational modifications of DNA and histones and influence metabolic gene expression. These enzymes require metabolites that are used as cofactors and substrates to carry out reactions. This interaction of epigenetics and metabolism constitutes a new avenue of cancer biology and could lead to new insights for the development of anti-cancer therapeutics.